Community Participation in Flood Management Systems in Aceh Utara Regency - Rahman, Bobby; Akmal , M.; Muzaffarsyah , Teuku; Yunanda , Rizki (Journal of Ecohumanism, 2024)
Flooding remains a persistent challenge in Aceh Utara Regency, representing a complex, cross-sectoral issue. If not addressed through collaboration among various stakeholders, including community groups, it has the potential to lead to new societal problems. This research seeks to assess the effectiveness and impact of using a participatory model in flood management efforts in the region. A qualitative approach was employed, gathering data through in-depth interviews with stakeholders such as local communities, government authorities, and non-governmental organizations involved in flood mitigation programs. The findings emphasize the urgency of adopting a participatory model to enhance the effectiveness of flood management systems. Actively engaging the community in planning, execution, and evaluation processes leads to a deeper understanding of local conditions, needs, and suitable solutions. Key aspects of the participatory model include raising public awareness of flood risks and mitigation measures, improving flood management infrastructure based on community input, creating more accessible and effective evacuation plans, and strengthening the community’s capacity for emergency response and simple mitigation efforts. In conclusion, this study aims to further explore the relevance and effectiveness of the participatory model in flood management in Aceh Utara Regency, ensuring the long-term sustainability of the region’s disaster management system.